2014
DOI: 10.1097/tp.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Conversion to Active Waitlist Status Among Temporarily Inactive Obese Renal Transplant Candidates

Abstract: Our findings indicate that half of obese status 7 candidates with a weight inappropriate for transplantation will not achieve active waitlist status. BMI at listing had a strong association with conversion to active status; comorbid factors and regional variation also impact activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…,27 Future studies directly comparing mortality rates in patients with ESRD after bariatric surgery with the rates of those who did not undergo surgery, and those patients with ESRD who had weight loss without bariatric surgery, may provide more insight into the obesity paradox.In addition to improvement in comorbidities, SG also helped increase patient access to transplant. Our rate of deactivation from the list after initial activation in patients who had undergone SG was 22.5%, similar to findings in obese patients on the waitlist who had not undergone SG 28. Our rate of deactivation from the list after initial activation in patients who had undergone SG was 22.5%, similar to findings in obese patients on the waitlist who had not undergone SG 28.…”
supporting
confidence: 81%
“…,27 Future studies directly comparing mortality rates in patients with ESRD after bariatric surgery with the rates of those who did not undergo surgery, and those patients with ESRD who had weight loss without bariatric surgery, may provide more insight into the obesity paradox.In addition to improvement in comorbidities, SG also helped increase patient access to transplant. Our rate of deactivation from the list after initial activation in patients who had undergone SG was 22.5%, similar to findings in obese patients on the waitlist who had not undergone SG 28. Our rate of deactivation from the list after initial activation in patients who had undergone SG was 22.5%, similar to findings in obese patients on the waitlist who had not undergone SG 28.…”
supporting
confidence: 81%
“…Of note, these reports reveal epidemiological associations but do not prove causation nor do they differentiate between intentional and unintentional weight loss. On the other hand, the presence of obesity lowers the likelihood of being waitlisted for kidney transplantation (6,7). Intentional weight loss also offers the potential of improving quality of life and/or ameliorating illnesses as in the general populace, though studies demonstrating this are thus far lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The study entry date was April 24, 2006, which was the first recorded date on the waitlist history file. As previously described, adult kidney transplant candidates (age ≥ 18) with a BMI ≥ 30 kg/m 2 and designated within 90 days of initial registration as status 7 due to a 'weight inappropriate for transplantation' were selected after excluding those with multiple listings, missing BMI, and clinically implausible BMI, defined as a BMI ≥ 65 kg/m 2 (n = 1,679) [18] . Among the 1,679 candidates, 328 received kidney transplants during the study period and comprised the exposure group (status 7).…”
Section: Study Populationmentioning
confidence: 99%
“…Using competing risks methods, we found that 49% of these candidates converted to active status within 6 years, with 61% of activated candidates receiving a transplant within 6 years of initial registration. Of the remaining candidates, 15% died, 21% delisted, and 15% continued in inactive status [18] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation